Blindness in the Johannine Tradition - Lieu, J. M. (New Testament studies, 1988)
That blindness should be a theme in the Johannine literature need cause no surprise; with the dualism of light and darkness and with the emphasis on what has been seen, witnessed and believed, the surprise is rather that the theme is not more prevalent. Only at two places in the Gospel and one in the Epistles is the language of blindness explicitly used, in John 9, John 12. 40 and 1 John 2. 11. However, since each of these can be seen as a focal point or interpretative key to the Johannine tradition the theme could be held to present in microcosm the history of the Johannine community. Chapter 9, the healing of the blind man, has played a central role in recent reconstructions of that history, while the reflection on the effects of Jesus's public ministry in 12. 37–50, before he turns away to address ‘his own’, invites similar treatment. Finally, the redirection towards internal opposition of language originally aimed outwards has long been seen as a mark of 1 John and as central to its interpretation. The exploration of the theme may serve in the same way to test in microcosm the presuppositions and results of such reconstruction. It also does more than this, for the imagery of blindness is by no means unique to John and raises clearly the question of the origins as well as of the context of Johannine thought.